2004
DOI: 10.1109/tnsre.2004.827225
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for improved muscle activation patterns after retraining of reaching movements with the MIME robotic system in subjects with post-stroke hemiparesis

Abstract: Previously, we reported that chronic stroke subjects had significant improvements in isometric strength, free reaching extent, and clinical evaluations of function after training in the mirror-image movement enabler (MIME) robotic device. Our primary goal in this analysis was to investigate the hypothesis that the robotic training promoted improved muscle activation patterns. To this end, we examined the interaction forces, kinematics, and electromyograms recorded during training of eight different movement pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(133 citation statements)
references
References 21 publications
3
129
0
1
Order By: Relevance
“…Sessions began with practice of targeted, twodimensional reaching movements at table level and then progressed to more complex, three-dimensional, out-ofsynergy movements beginning at table level and ending at eye level. Movement patterns incorporated into the training sessions have been previously described [6]. Representative beginning and ending arm positions are shown in Figure 1.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sessions began with practice of targeted, twodimensional reaching movements at table level and then progressed to more complex, three-dimensional, out-ofsynergy movements beginning at table level and ending at eye level. Movement patterns incorporated into the training sessions have been previously described [6]. Representative beginning and ending arm positions are shown in Figure 1.…”
Section: Interventionmentioning
confidence: 99%
“…Two previous clinical trials demonstrated significantly greater gains in motor recovery [4][5][6][7][8], as measured by proximal upper-limb FuglMeyer Assessment (FMA) of motor function [9] scores, at posttreatment in the RA training group than in the control group (CG). However, in both studies the gains in the RA and CGs were equivalent at the 6-month follow-up evaluations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a study of the electromyography (EMG) patterns after training with an end point tunnel controller, a compensatory strategy using excessive shoulder girdle movement appeared to compromise learning of normal reaching patterns [46]. Use of proximal joints in compensatory strategies can be made ineffective with an appropriate control law and an exoskeleton that has direct control of arm joints.…”
Section: Introductionmentioning
confidence: 99%
“…Another robot aimed at training movements in the shoulder and elbow joints was the Mirror Image Movement Enabler (MIME), developed at Stanford University (USA) [49,50]. This robot allowed training in passive, active-assisting, active-coercion and bimanual modes.…”
mentioning
confidence: 99%